Expériences paysagères et pratique du ski de randonnée dans les Alpes françaises - Stéphane Marpot; Laine Chanteloup; Clémence Perrin-Malterre (Projets de Paysage)
In this article, we propose to examine the landscape experiences of cross-country skiers visiting various alpine mountain ranges. We will show that, for these skiers, the landscape can be considered in several ways. First, through the way it is perceived via different registers of knowledge, from imagined adventure stories to nivological and topographical knowledge. Then, by studying traces in the snow made by skiers, traces sketched in the snow by bodies propelled on skis, we seek to discover a contemporary relationship between the body and landscape. Cross-country skiing is a practice engaging different landscape experiences we will explore via an anthropological approach focusing on the logic of incorporation and the ecological expression of the body. This landscape experience will challenge a vision-centric definition of the landscape in order to apprehend the landscape as determined by human perception and, above all, as determined by the relationships formed and materialised between existing elements (animals, plants, abiotic elements). Far from a passive contemplation in which only vision is predominant, "making beautiful or fine traces" entirely engages the practitioners in a physical capacity. Ultimately, this practice invites us to raise the questions how people learn different ways of feeling about and acting within the environment and looks at a creative form of composing elementary landscapes.